2020
DOI: 10.7717/peerj.9993
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pediatric scoring systems for mortality in septic patients and the impact of missing information on their predictive power: a retrospective analysis

Abstract: Background Scores can assess the severity and course of disease and predict outcome in an objective manner. This information is needed for proper risk assessment and stratification. Furthermore, scoring systems support optimal patient care, resource management and are gaining in importance in terms of artificial intelligence. Objective This study evaluated and compared the prognostic ability of various common pediatric scoring systems (PRIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…The study flow diagram is shown in Figure 1 . A total of 29 studies were included for quantitative synthesis, among them, 18 studies that reported on the scoring systems PRISM-III/IV, ( 3 , 4 , 11 , 14 – 21 , 23 27 , 37 ), 11 studies that reported data on PIM-3 ( 3 , 4 , 7 , 14 , 16 , 18 , 20 , 28 – 31 ), and nine studies that reported data on PELOD-2 ( 5 , 14 , 16 , 28 , 32 36 ). Four studies were reported from India ( 4 , 7 , 17 , 34 ), two from Australia ( 20 , 32 ), two from China ( 20 , 32 ), two from Egypt ( 15 , 18 ), one from Pakistan ( 19 , 26 ), two from Korea ( 14 , 36 ), one from Mexico ( 21 ), one from Singapore ( 28 ), one from UAE ( 29 ), one from Indonesia ( 30 ), one from Africa ( 33 ), one from Saudi Arabia ( 11 ), two from Turkey ( 22 , 24 ), one from Sweden ( 23 ), one from Brazil ( 37 ), one from Switzerland ( 5 ), one from Thailand ( 27 ), one from Italy ( 31 ), and one multi-centric ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study flow diagram is shown in Figure 1 . A total of 29 studies were included for quantitative synthesis, among them, 18 studies that reported on the scoring systems PRISM-III/IV, ( 3 , 4 , 11 , 14 – 21 , 23 27 , 37 ), 11 studies that reported data on PIM-3 ( 3 , 4 , 7 , 14 , 16 , 18 , 20 , 28 – 31 ), and nine studies that reported data on PELOD-2 ( 5 , 14 , 16 , 28 , 32 36 ). Four studies were reported from India ( 4 , 7 , 17 , 34 ), two from Australia ( 20 , 32 ), two from China ( 20 , 32 ), two from Egypt ( 15 , 18 ), one from Pakistan ( 19 , 26 ), two from Korea ( 14 , 36 ), one from Mexico ( 21 ), one from Singapore ( 28 ), one from UAE ( 29 ), one from Indonesia ( 30 ), one from Africa ( 33 ), one from Saudi Arabia ( 11 ), two from Turkey ( 22 , 24 ), one from Sweden ( 23 ), one from Brazil ( 37 ), one from Switzerland ( 5 ), one from Thailand ( 27 ), one from Italy ( 31 ), and one multi-centric ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…A study reported by Zhong et al ( 32 ) reported that the PELOD-2 score was effective to assess the prognosis of PICU patients with sepsis and has shown an excellent discriminatory power with 0.916. On the other hand, PRISM-III/IV score and PELOD-2 performance becomes better when sepsis is pronounced ( 16 ). Another study reported by Mathews et al showed that the PELOD-2 score of over 20 was able to predict mortality in 72.2% of PICU patients, and the cut-off score >16 showed a sensitivity of 100% and specificity of 54.1% ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…They reported fair discriminating ability (AUROC, 95% CI) of PIM (0.76 [0.68-0.76]), PIM-2 (0.78 [0.72-0.78]), PIM-3 (0.76 [0.68-0.76)]), PRSIM-III (0.75 [0.68-0.75]), and PELOD-2 (0.75 [0.66-0.75]), while PELOD-2 (AUROC-0.84[0.77-0.91]) and PRISM-IV (AUROC 0.8[0.72-0.88]) had good discriminative ability. 35 Some limitations of our study must be addressed. Since this is a single-center retrospective study with a small sample size, the results may not generalize to other centers or populations.…”
Section: Discussionmentioning
confidence: 96%
“…PIM, PIM2, and PIM3 scores, together with PRSIM III and PELOD 2, provided the most suitable indications of mortality, while PRISM provided the poorest mortality prediction of all the tested scores [ 25 ]. Based on the daily estimation of the severity of multiple organ dysfunction syndromes in critically ill children, a high PELOD score (≥ 20 points) was associated with a mortality rate of 40.7%, and a low PELOD score (< 10 points) was associated with a mortality rate of < 1% on the first day of PICU admission [ 26 ].…”
Section: Discussionmentioning
confidence: 99%